Covalent and Noncovalent Dimers of the Cyanide-Resistant Alternative Oxidase Protein in Higher Plant Mitochondria and Their Relationship to Enzyme Activity. - Umbach, A. L. (1993)
Evidence for a mixed population of covalently and noncovalently associated dimers of the cyanide-resistant alternative oxidase protein in plant mitochondria is presented. High molecular mass (oxidized) species of the alternative oxidase protein, having masses predicted for homodimers, appeared on immunoblots when the sulfhydryl reductant, dithiothreitol (DTT), was omitted from sodium dodecyl sulfate-polyacrylamide gel sample buffer. These oxidized species were observed in mitochondria from soybean (Glycine max [L.] Merr. cv Ransom), Sauromatum guttatum Schott, and mung bean (Vigna radiata [L.] R. Wilcz). Reduced species of the alternative oxidase were also present in the same mitochondrial samples. The reduced and oxidized species in isolated soybean cotyledon mitochondria could be interconverted by incubation with the sulfhydryl reagents DTT and azodicarboxylic acid bis(dimethylamide) (diamide). Treatment with chemical cross-linkers resulted in cross-linking of the reduced species, indicating a noncovalent dimeric association among the reduced alternative oxidase molecules. Alternative pathway activity of soybean mitochondria increased following reduction of the alternative oxidase protein with DTT and decreased following oxidation with diamide, indicating that electron flow through the alternative pathway is sensitive to the sulfhydryl/disulfide redox poise. In mitochondria from S. guttatum floral appendix tissue, the proportion of the reduced species increased as development progressed through thermogenesis.